FENOMENA DIBALIK KESUKSESAN IKLAN TESTIMONI; Testimony Behind Advertising Phenomenonof Success - Mandemasya, Herna (Universitas Prof. Dr. Moestopo (Beragama), 2013)
This study focused to see how audiences can produce the meaning of a testimonial ad impressions. By taking a qualitative approach, the study sought to examine the factors which involved the public in decision-making process to use the advertised product.Theories about the audience, meaning transfer theory and the theory of marketing communications, particularly in terms of interpretation of the ad into a foundation for preparing the framework of thought, the underlying research and studies addressing this.The results showed that the form of testimony or the testimony ad can increase confidence in the product Top1. The testimony of many of the characters makes the audience to not believe in his testimony. Credible leaders are needed for ads with this type of testimony, thus affecting the public to use and remain loyal to the product being advertised. Efforts should be made, in search of a credible figure for testimonial advertising tracking study needs to be done to the public. Psychological factors, self concept, individual background, and the environment can not be separated from the meaning of a text in the ad. Visual language in their ads that highlight the symbols of a champion and education about synthetic oil meant the same as expectations of advertisers. For the meaning of Top1 advertising, audiences hold a social context with an expert before deciding to construct meaning using the product. This is related to Top1 product which is a type of high involment or high involvement.